Infection by cytauxzoon spp. In domestic felines - Ribeiro, Taiã Mairon Peixoto; Santos, Helcileia Dias; Reis, Thássia Silva; Sousa, Sebastiana Adriana Pereira; Furquim, Maria Eduarda Chiaradia [UNESP]; André, Marcos Rogério [UNESP]; Jayme, Valéria de Sá (Medicina Veterinaria (UFRPE), 2019)
Cytauxzoon spp. are piroplasms, hemoparasites parasitizing specimens of the Felidae family. Cytauxzoonosis is a disease characterized mainly by nonspecific and sudden clinical signs. It has as reservoirs the wild felids, however there are already reports of chronic parasitemia in domestic felines. Transmission occurs mainly by vectors such as ticks in North America; but in South America, Europe, and Asia, the vectors are still unknown. The pathogenesis stems from the schizogony stage of the parasite in macrophages that causes obstruction of blood vessels. Treatment is based on supportive care and the combination therapy of atovaquone associated with azithromycin has shown good results. Prophylaxis consists in restricting the access of domestic cats to wooded areas with the presence of ticks and the use of repellents and acaricides. With this literature review, the objective was to analyze the epidemiological, clinical, and pathological aspects that allow the veterinarian to act quickly in cases suspected of cytauxzoonosis.
Infecção por cytauxzoon spp. Em felinos domésticos
Keywords: Cats; Cytauxzoonosis; Felidae